Gender-Related Difference in D-Dimer Level Predicts In-Hospital Heart Failure after Primary PCI for ST-Segment Elevation Myocardial Infarction. (11th August 2021) - Li, Li; Wang, Wei; Li, Tai; Sun, Ying; Gao, Yanjun; Wang, Lin; Yao, Heng-Chen
Abstract : Aims . The prognostic value of plasma D-dimer in patients with coronary artery disease (CAD) remains controversial. The study is aimed at investigating the relationship between plasma D-dimer levels and in-hospital heart failure (HF) in ST-segment elevation myocardial infarction (STEMI) patients who underwent primary percutaneous coronary intervention (pPCI). Methods . STEMI patients who underwent pPCI were enrolled in this study. Venous blood samples were collected from patients on admission before pPCI procedure. The study endpoint was the occurrence of in-hospital HF. The participants were divided into two groups according to plasma D-dimer levels and further compared baseline D-dimer levels between male and female. Logistic regression and receiver operating characteristic (ROC) curves were performed to evaluate the relationship of D-dimer and in-hospital HF. Results . A total of 778 patients were recruited in the study, of which 539 (69.3%) patients had normal D-dimer levels (≤0.5 mg/L) while 239 (30.7%) had increased D-dimer levels (>0.5 mg/L). The female patients have higher D-dimer levels and higher incident rate of in-hospital HF than that in male patients (p < 0.001 ). The multivariate logistic regression model revealed that D-dimer was an independent predictor for in-hospital HF in overall population (adjusted odds ratio [OR]: 1.197, 95% CI: 1.003-1.429, and p = 0.046 ) and female patients (adjusted OR: 1.429, 95% CI: 1.083-1.885, and p = 0.012 ). Conclusion . Increased plasma D-dimer levels were an independent risk factor for incidence of in-hospital HF in STEMI patients who underwent pPCI, especially in female patients, which provides guidance for clinicians in identifying patients at high risk of developing HF and lowering their risk.